Editorial [Is Suicidality Serious?] - Besag, Frank M.C. (Current Drug Safety, 2009)
If the man in the street were to be asked this question, his response might well be as follows. “Of course it must be serious. Is your question a serious one?” It seems self-evident that suicidality must be taken seriously. However, like many things that appear to be self-evident, the seriousness of the concept of suicidality should be questioned. The first step in trying to answer the question posed in the title of this editorial must be to define the concept of “suicidality”. The “Wiktionary” (web-based dictionary) defines suicidality as “the tendency of a person to commit suicide” or “a fatality that is an instance of suicide”. The Oxford English dictionary defines suicidality as “the quality or condition of being suicidal”. Do these terms accurately reflect the meaning of the word “suicidality” as used in the medical literature? It would appear that the answer is, emphatically, no. A commonly used definition in the medical literature is “suicidal acts or ideation”. Silverman et al. use the operational definition “considered suicide, attempted suicide” [1]. In a review of the reported link between suicidality and the use of SSRIs, we defined the term as “suicidal ideation, self-harm and suicide attempt” [2]. In other papers, suicidality is not defined but, by implication, it appears to be defined as “suicidal ideation, intent or attempt”. Are these definitions simply too broad to be of practical use? Suicidal ideation might include anything from a transient thought that life is not worth living to a persistent determination to end life with a clear plan, using a means that is very likely to be effective, such as jumping off a high building. Similarly, suicide attempt might cover anything from being seen in an accident and emergency department for having taken more than the recommended dose of aspirin through to shooting oneself in the head with non-fatal consequences. Most people who make apparent suicidal gestures do not seriously wish to end their lives but instead want to draw attention to their difficult predicament. Should this situation be classified as “suicide attempt” or should another term, such as “deliberate self-harm” be preferred? The problem with the term “deliberate self-harm” is that it would normally include a much wider variety of behaviours, for example, self-cutting, that are carried out with no intention of suicide.